UJI AKTIVITAS ANTIBAKTERI EKSTRAK BUNGA KECOMBRANG (Etlingera elatior (Jack) R. M.Sm.) TERHADAP BAKTERI Staphylococcus aureus Sp. - Rusdiati Helmidanora; Yullia Sukawaty; Divya Miranti; Tria Prayoga; Nia Lisnawati (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2024)
Kecombrang plant contains essential oils which are bioactive, including 0.0735% in the leaves. in flowers 0.0334%, in stems 0.0029% and in rhizomes 0.0021%. Combrang flowers (Etlingera elatior (Jack)) have effective antibacterial activity. The aim of this research was to determine the level of ethanol extract of kecombrang flowers from Pampang village (100-500 masl), East Kalimantan in inhibiting Staphylococcus aureus bacteria. The object studied was the inhibitory zone of kecombrang flower extract against Staphylococcus aureus bacteria. Extract preparation was carried out using the maceration method using 96% ethanol solvent, antibacterial activity testing was carried out using the well method with extract concentrations of 10%, 20%, 40%, 60% and positive control chloramphenicol and negative control DMSO. The results of this study were that 96% ethanol extract of kecombrang flowers had antibacterial activity against Staphylococcus aureus bacteria with a maximum concentration of 60% and had a medium category inhibitory power of 5.933 mm.